Motivational Factors of the Collaborative Consumption in the Era of Sharing Econmy - Iin Mayasari; Handrix Chrisharyanto (Gadjah Mada International Journal of Business, 2018)
The aim of this study was to analyze the motivational factors of collaborative consumption in the era of the sharing economy, as a part of consumers’ behavior by online media platforms. Collaborative consumption is about people’s willingness to share and to collaborate to meet certain needs. The study used the qualitative method with interviews for the data’s collection. The context of the study was using consumers who had experience of using Airbnb, Go-Jek, and selling their product via online media. Twenty-four respondents were obtained for the interviews. The length of each interview was approximately 1.5 hours. The analysis of this shifting consumption across its different facets provided an analysis of the motivational aspect of sharing resources, and the change in consumer consumption patterns. The motivational research examined the underlying reasons for consumers to act, and to undertake collaborative consumption; home sharing and selling second-hand goods were analyzed from the perspectives of their economic aspects, utility reasons, social orientation, emotional aspects, ecological aspects and personal values.